The impact of religious behaviours on the health and well-being of emerging adults - Kirk, Chris Michael (Mental health, religion & culture, 2013)
Emerging adulthood is a life stage in which the frequency of religious behaviours often wanes while the risk of mental illness, substance abuse, and risky sexual behaviour increases. The current study explores the role that religious behaviours might play in mitigating these risks among college-attending emerging adults. Survey data were collected on religious service attendance, prayer and meditation, substance use, sexual activity, and life satisfaction. Results revealed a significant effect for religious service attendance on substance use and sexual behaviour and for the frequency of prayer/meditation on life satisfaction, marijuana use, and sexual intercourse. Group comparisons revealed that emerging adults who participated in religious activities reported lower rates of substance use, less sexual behaviour, and greater satisfaction with life. Limitations and suggestions for future research are discussed.